Talent in sports. Some reflections about the search for future champions - Buekers, M.; Borry, P.; Rowe, P. (Movement & Sport Sciences - Science & Motricité, 2015)
The goal of this paper is to look into the issue of talent identification in sports. Over the last decade researchers tried to get a better insight into how future elite athletes can be selected at young age. The findings reported in this review reveal that elite athletes originate from an optimal combination of intrinsic competences (e.g., physical, technical, psychological) and extrinsic, contextual factors (e.g., training, parents). The identification process that focuses on measuring intrinsic competences should be multidimensional in nature. Moreover, valid interpretations of the potential of the youngsters require longitudinal testing. Finally, the best talent detection program will be useless unless a high quality follow-up is guaranteed through well-designed training programmes in which coaches and PE-teachers play a crucial role. Therefore, the interaction and cooperation of coaches and scientists offer great opportunities to advance the knowledge in the area of talent identification.